2013
DOI: 10.1007/s11060-013-1294-0
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of temozolomide versus radiotherapy in elderly glioblastoma patients

Abstract: Temozolomide (TMZ) alone has been proposed as a promising alternative to radiotherapy (RT) in elderly glioblastoma (GBM) patients. We report a meta-analysis to systematically evaluate TMZ monotherapy in older GBM patients. A systematic literature search was performed using PubMed, EMBASE and the Cochrane database. Studies comparing TMZ versus RT in elderly patients (≥ 65 years) with newly diagnosed GBM were eligible for inclusion. Two randomized clinical trials (RCTs) and three comparative studies were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…In addition, neither mgmt methylation status nor IDH1/2 mutation status testing was available during the study period. Both markers have been shown to have significant prognostic and predictive value in patients with gbm, and mgmt methylation status in particular has been shown to predict response to temozolomide [22][23][24][25] . In ce.6, elderly patients with mgmtmethylated tumours showed the greatest survival benefit with combined therapy 2 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, neither mgmt methylation status nor IDH1/2 mutation status testing was available during the study period. Both markers have been shown to have significant prognostic and predictive value in patients with gbm, and mgmt methylation status in particular has been shown to predict response to temozolomide [22][23][24][25] . In ce.6, elderly patients with mgmtmethylated tumours showed the greatest survival benefit with combined therapy 2 .…”
Section: Figurementioning
confidence: 99%
“…In elderly patients who are less likely to tolerate combined chemoradiotherapy, mgmt methylation status might be especially important. The use of temozolomide monotherapy in mgmt-methylated patients is an area of active study in elderly patients with gbm 25 .…”
Section: Figurementioning
confidence: 99%
“…In certain cases, concurrent TMZ has been added to HRT, based on the superior outcomes reported with the Stupp protocol (7,8), although it has not yet been established that combining HRT with concurrent TMZ is superior to HRT alone (9). More recently, TMZ was investigated as a single agent and, based on certain genetic factors in the tumor, it may also be an effective treatment option (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, chemotherapy with TMZ alone is put forth as an acceptable alternative to RT in elderly patients with GBM [32,33,34,35]. The NOA trial examined and compared patients who received TMZ-alone ( n = 195) versus RT-alone ( n = 178) for malignant astrocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although these trials demonstrated the non-inferiority of TMZ compared to RT in elderly patients; they did not compare the outcome of TMZ when used as an adjuvant treatment to RT. Yin et al [32] also demonstrated the non-inferiority of TMZ to RT-alone in improving the overall survival in elderly, however at an increased risk of grade 3-4 toxicities. Zarnett et al [33], in their systematic review, concluded that elderly patients with MGMT promoter methylation are more likely to receive the greatest benefit from TMZ-alone regimen over RT.…”
Section: Discussionmentioning
confidence: 99%